2017
DOI: 10.1111/1744-9987.12486
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Body Water in the Efficacy of Convective Solute Transport in Online Hemodiafiltration

Abstract: High-volume online hemodiafiltration (OL-HDF) has been associated with improved patient survival compared to conventional hemodialysis in recent trials, where the importance of convective volume (CV) in this benefit is noted. The purpose of this study was to determine the corporal composition parameters influencing the efficacy of CV in the removal of different molecular weight (MW) molecules. Demographic data, corporal composition parameters with bioimpedance spectroscopy, dialysis features and the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Davenport et al reported that an associated survival advantage for higher CV was observed when the CV was adjusted according to body surface area or TBW, using surrogate estimates of lean body mass, rather than body weight or BMI (which is more related to fat mass), in patients on Post‐OL‐HDF 6 . Consistent with previous reports on CV adjusted to body water in Post‐OL‐HDF, 7,8 we found that CV/ECW, CV/TBW and CV/ICW, but not CV alone, were significantly associated with RRs of β2‐microglobulin and α1‐microglobulin in patients on Pre‐OL‐HDF. The importance of body water in the efficacy of RRs of β2‐microglobulin and α1‐microglobulin in Pre‐OL‐HDF was confirmed in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Davenport et al reported that an associated survival advantage for higher CV was observed when the CV was adjusted according to body surface area or TBW, using surrogate estimates of lean body mass, rather than body weight or BMI (which is more related to fat mass), in patients on Post‐OL‐HDF 6 . Consistent with previous reports on CV adjusted to body water in Post‐OL‐HDF, 7,8 we found that CV/ECW, CV/TBW and CV/ICW, but not CV alone, were significantly associated with RRs of β2‐microglobulin and α1‐microglobulin in patients on Pre‐OL‐HDF. The importance of body water in the efficacy of RRs of β2‐microglobulin and α1‐microglobulin in Pre‐OL‐HDF was confirmed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Effects of higher convection volume (CV) on nutritional status, body compositions and survival advantage have drawn attention in Post‐OL‐HDF 5,6 . However, CV has different effects on the elimination of solutes that depend on the patient's fluid composition 7 . Macías et al reported that the ratios of CV/extracellular water (ECW) 7,8 and CV/total body water (TBW), 8 but not CV alone, were independent predictors for higher elimination of β2‐microglobulin and other protein‐bound uraemic toxins in patients on Post‐OL‐HDF 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Correlation of clinical beta‐2 microglobulin reduction ratio (β 2 M RR) data and sieving coefficient using (A) values reported in data sheets and instructions for use and (B) values measured under identical testing conditions (per the methodology stated in ISO 8637, using human plasma with Q B /UF of 300/60mL/min) . HD, hemodialysis; HDF, hemodiafiltration.…”
Section: Resultsmentioning
confidence: 99%